PERTUMBUHAN SEMAI MAHONI (Swietenia macrophylla King) PADA BERBAGAI DOSIS FUNGI MIKORIZA ARBUSKULAR (Glomus mosseae) - Hijrawati, Hijrawati; Yusran, Yusran; Rahmawati, Rahmawati (Universitas Tadulako, 2015)
Swietenia macrophyllah King is known as wide leaf including Meliaceae family. Mahoni wood has many functions such as furniture material, ship material, pattern maker, crafts, and traditional medicine. Many medical treatments have used this plant traditionally. Micoriza is a mutualism symbiosis between fungi and high level of plant root system aims to find out the response of mahoni seedling growth (Swietenia macrophyllah King) toward the application of various arbuscular micoriza fungi dozes. The research was conducted from December 2013 to February 2014 in Green House and Forestry Sciences Laboratory, Forestry Faculty, Tadulako University, Palu of Central Sulawesi. It employed Complete Random Design method (RAL) consisting of 5 treatments namely: M0 = without micoriza application (control), M1= Glomus mosseae 5g/seedling, M2= Glomus mosseae 10g/seedling, M3= Glomus mosseae 15g/seedling, M4= Glomus mosseae 20g/seedling. Those five treatments were repeated as 10 times so the total is 50 units of treatments. The result indicates that the giving of various dozes of FMA significantly influence toward the parameter of high growth, diameter, leaves number, and dry weight, mahoni seedling leading of nine weeks after planted, however, it is not significantly influence toward the parameter of other plants growth such as leading wet weight, root wet weight, or the root dry weight. The dozes 20 grams/seedling give response to seedling growth mahoni better than the other dozes or the control. Keywords: Doses, Fungi mycorrhizal arbuscular (FMA), Swietenia macrophylla King.